Use of PCR in the amplification of the rpoB gene of some Philippine mycobacterium tuberculosis isolates and SSCP analysis of rimfampicin resistance - Dalet, Jay T
Mycobacterial rpoB gene is the structural gene that codes for the synthesis of bacterial RNA polymerase. Presence of mutations in the rpoB gene of Mycobacterium tuberculosis alters the sequence of amino acids in bacterial RNA polymerase essential for rifampicin binding. Such mechanism allows for Mycobacterium tuberculosis resistance to rifampicin. To detect the presence of mutations in the rpoB gene, 411 bp fragment of the rpoB gene coming from 18 rifampicin resistant (11 hospital and 7 community isolates) 11 rifampicin sensitive (7 hospital 4 community isolates) Mycobacterium tuberculosis (Mtb) isolates were amplified by PCR (polymerase chain reaction) using TR1 and TR2B primers of Telenti and were subjected to single strand conformation polymorphism (SSCP) analysis. H37Rv a virulent sensitive strain of Mtb was used as the reference strain. PCR conditions were optimized in two different thermal cyclers GeneAmp and Master Cycler using 4mM and 2.5 mM MgCI 2 respectively. PCR reaction was run for 30 cycles using GeneAmp (5 min at 94oC, 30s at 55 oC, 30s at 72oC) fo9llowed by 10 minutes of final extension at 72oC. In the Master Cycler the reaction was run for 30 cycles (5 min at 95oC, 20s at 95oC, 20s at 60oC, 30s at 72oC) followed by 10 minutes of final extension at 72oC. SSCP analysis of Mtb isolates was carried out under manual and semi-automated procedures. A clear distinction between the sensitive isolates and resistant isolates were not clearly established under manual SSCP conditions. 2 sensitive isolates (1459H and 46aH) demonstrated two different mobility patterns. Despite the presence of minor shifts, similar patterns were found between sensitive isolate 1459H and resistant isolate 24H; and between sensitive isolate 46aH and resistant isolate 455bR1 H. Using the semi-automated PCR-SSCP analysis, 8 sensitive isolates demonstrated a consistent pattern when run under 7oC (1463H and 344C) and 10oC (244C, 1463H, 240C, 2122aH, 255C, 1224H). At constant temperature of 7oC using DSFebX denaturing solution, four (1807H, 1348H, 333C, 267C) out of five rifampicin resistant strains demonstrated polymorphisms which were distinct from the pattern of the two rifampicin sensitive isolates. One rifampicin resistant isolate (1365H) had a very similar pattern with that of the sensitive isolates. But at a constant temperature of 10oC using DS3 denaturing solution, all nine (333C, 2321H, 270C, 276C, 473DC, 1259H, 1400H, 306C) rifampicin resistant isolates demonstrated polymorphisms which are distinct from the consistent pattern demonstrated by 6 rifampicin sensitive isolates. The PCR-SSCP product coming from H37Rv exhibited an electro-mobility pattern similar to that of the rifampicin sensitive isolate (1224H) that exhibited a consistent pattern with the other rifampicin sensitive isolates. The consistent pattern achieved among all 6 sensitive isolates and te polymorphisms among the 9 rifampicin resistant strains suggest that the SSCP temperature condition is optimum at 10oC with the use of DS3 denaturing solution; that mutations are present in the amflified 411 bp fragment of the Mtb rpoB gene of the 9 rifampicin Mtb resistant Mtb isolates. These are confirmatory to the phenotypic resistance determined by the drug sensitivity testing for the 9 rifampicin resistant Mtb isolates. Similarities in the prominent PCR-SSCP bands were exhibited by 3 rifampicin resistant isolates 333 CS, 2321R1 HS, and 270 CS; 3 rifampicin sensitive isolates 244 CS, 240 CS and 1463 HS and 2 rifampicin sensitive isolates 2122a HS and 255 Cs. Presence of several polymorphic patterns in the resistant isolates other than the two major prominent bands suggests that the mutations harbored by the Mtb rpoB gene are different point mutations that alters the key amino acid sequence in the Mtb RNA polymerase. PCR-SSCR analysis at 10oC revealed six polymorphic variants among the rifampicin resistant Philippine Mtb isolates and one consistent pattern among the 6 rifampicin sensitive Philippine Mtb isolates which either came from the Lung Center of the Philippines or Department of Health.